Analysis and evaluation of capital adequacy in Latvian banking system - Konovalova, Natalia; Dalecka, Snezhana (Copernican Journal of Finance & Accounting, 2016)
Regulation of banking activity under economic insecurity conditions is one of key problems in our times and is acquiring a particular importance both for banks themselves and their shareholders and also for customers and depositors. Instability of economic situation gives birth to increasing risks faced by world banking system. And therefore in order to ensure reliable operation of commercial banks and prevent their vulnerability to economic insecurity, the supervisory bodies are continuously improving the methods of and approaches towards the management of bank risks accenting a paramount importance of own capital adequacy. A problem of how much capital Latvian commercial banks need to cover their risks remains one of most important in regulation and assessment of banking activity. Meanwhile, the principal direction to improve the capital adequacy ratio is the growth in its flexibility when determining the value of risks inherent to various bank organisations. In the present research authors carry out the analysis of risks inherent in activity of Latvian commercial banks, indentifies the risk pattern within own capital of banks, discovers factors having impact upon the risk pattern as well as estimates the amount of capital necessary to cover risks in various groups of commercial banks. Hypothesis – Stability of a banking system depends on the level of sufficiency of a bank capital. The aim of the research: Evaluation of capital adequacy of Latvian commercial banks and correspondence of capital adequacy calculations to Basel Committee on Banking Supervision rules based on analysis of financials statements, identification of capital adequacy problems and developing recommendations on improving bank capital adequacy according to the effective and the planned Basel Committee on Banking Supervision requirements.